2019
DOI: 10.1038/s41419-019-1649-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ncRNA targeting induces cell cycle arrest and tumor growth inhibition of MDA-MB-231 breast cancer cells through reduction of key cell cycle progression factors

Abstract: The family of long noncoding mitochondrial RNAs (ncmtRNAs), comprising sense (SncmtRNA), and antisense (ASncmtRNA-1 and ASncmtRNA-2) members, are differentially expressed according to cell proliferative status; SncmtRNA is expressed in all proliferating cells, while ASncmtRNAs are expressed in normal proliferating cells, but is downregulated in tumor cells. ASncmtRNA knockdown with an antisense oligonucleotide induces massive apoptosis in tumor cell lines, without affecting healthy cells. Apoptotic death is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 50 publications
(74 reference statements)
7
60
0
Order By: Relevance
“…NcRNAs are non-coding parts of genome at different cell status, and account for more than 90% RNA transcripts [43]. Increasing data have demonstrated that ncRNAs played the important regulatory roles in many biological processes such as sex differentiation [44], organ development [45], and tumor origination and progression [46]. More and more studies revealed that ncRNAs played regulatory roles by ceRNA network on the basis of ceRNA hypothesis [21], and utilizing ceRNA network analysis have identified a lot of regulatory factors including lncRNAs, miRNAs and cirRNAs associated with some animal economic traits such as hair follicle cycle of cashmere goat and poultry meat quality [27,47].…”
Section: Discussionmentioning
confidence: 99%
“…NcRNAs are non-coding parts of genome at different cell status, and account for more than 90% RNA transcripts [43]. Increasing data have demonstrated that ncRNAs played the important regulatory roles in many biological processes such as sex differentiation [44], organ development [45], and tumor origination and progression [46]. More and more studies revealed that ncRNAs played regulatory roles by ceRNA network on the basis of ceRNA hypothesis [21], and utilizing ceRNA network analysis have identified a lot of regulatory factors including lncRNAs, miRNAs and cirRNAs associated with some animal economic traits such as hair follicle cycle of cashmere goat and poultry meat quality [27,47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the E2 oncogene is involved in this regulation [61]. Fitzpatrick et al demonstrated that the knockdown of ASncmtRNA induced cell death and inhibited tumor growth via cell cycle-related genes, such as cyclin B1, cyclin D1, CDK1, CDK4, and surviving in breast cancer cell lines [62]. Thus, these findings shed light on the functional role of ASncmtRNA in cancer progression.…”
Section: Mitochondrial Dna-encoded Lncrnas and Mitochondrial Functionmentioning
confidence: 97%
“…Chimeric lncRNAs containing mtDNA-encoded genes have been characterized. Sense mitochondrial ncRNA (SncmtRNA) is expressed in proliferating cells, including normal and cancer cells, but not in resting cells [61,62]. SncmtRNA has a characteristic RNAse-resistant double-stranded structure with a 40-nucleotide loop.…”
Section: Mitochondrial Dna-encoded Lncrnas and Mitochondrial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense RNA therapy is an emerging topic of translational research in medicine and currently the focus of many clinical trials in cancers, myopathies, Huntington's disease and many other diseases (Crooke et al, 2018). For example, a phase 1b clinical assay is currently under way for the treatment of solid cancers by an antisense oligonucleotide targeted to ASncmtRNA (Burzio et al, 2009;Lobos-González et al, 2016;Fitzpatrick et al, 2019;ClinicalTrials Identifier: NCT03985072). All these examples of ASOs in clinical trials show that the concept of antisense RNA therapy is coming of age and will be developed further in the near future thanks to its low toxicity, high specificity and low production cost.…”
Section: Introductionmentioning
confidence: 99%